Physical activity patterns following major lower limb amputation - Katarzyna Wójtowicz; Agata Walczak; Wiktoria Gajek-Flanczewska; Małgorzata Wirkijowska; Paulina Woźniak; Sebastian Flanczewski; Jakub Wirkijowski; Ewa Wietrzykowska; Martyna Śliwińska; Anna Podraza; Dominika Sobolewska; Katarzyna Michalczyk-Fraszka (Journal of Education, Health and Sport)
Introduction and aim of study: Lower limb amputation is one of the most common acquired disabilities. The main aim of the study was to assess global trends regarding the procedure, investigate the current trends in post-amputation care, particularly in terms of returning to physical fitness, and identify potential fields of interest in order to improve the everyday life of people with lower limb amputation.